2019
DOI: 10.1186/s12890-019-0960-1
|View full text |Cite
|
Sign up to set email alerts
|

Acute exacerbations of fibrosing interstitial lung disease associated with connective tissue diseases: a population-based study

Abstract: BackgroundAcute exacerbation (AE) is the major cause of morbidity and mortality in patients with idiopathic pulmonary fibrosis (IPF). AEs also occur in other forms of fibrosing interstitial lung disease (fILD). The clinical features and prognosis of AE patients with connective tissue diseases (CTDs) associated-ILD has not been fully described.MethodsWe retrospectively reviewed 177 patients with either IPF or a characterized CTD-ILD admitted to Nanjing Drum Tower Hospital with an AE from January 2010 to Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 42 publications
5
30
1
1
Order By: Relevance
“…demonstrated that the cut-off level of ΔLDH level of > 80 IU/L, as measured within 2 weeks, was related to poor prognosis. Furthermore, changes in LDH were reportedly associated with AE-related poor prognosis in patients with connective tissue disease associated with interstitial pneumonia [23]. Our study suggests that LDH change was useful as a prognostic factor.…”
Section: Discussionsupporting
confidence: 50%
“…demonstrated that the cut-off level of ΔLDH level of > 80 IU/L, as measured within 2 weeks, was related to poor prognosis. Furthermore, changes in LDH were reportedly associated with AE-related poor prognosis in patients with connective tissue disease associated with interstitial pneumonia [23]. Our study suggests that LDH change was useful as a prognostic factor.…”
Section: Discussionsupporting
confidence: 50%
“…[6][7][8] The studies mentioned above, however, did not use the current definition of AE-IPF in their inclusion criteria, and in addition, one study included patients treated in the ICU, 8 which is known to be a risk factor for death, at least in patients with IPF. 28 The other published studies concerning AE-FILD have been conducted in Japan, [9][10][11][12][13][14] of which only one demonstrated longer survival of patients with non-IPF compared with that of IPF 13 ; in another study, the prognosis of AE-IPF compared with other FILDs was even better. 9 Altogether, it can be stated that the earlier publications focusing on acute respiratory worsening or AE of IPF or non-IPF FILDs have consisted of small and heterogenic study populations with variable inclusion criteria, which complicate making comparisons between the investigations.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] The phenomenon of acute exacerbation (AE) has been associated with high mortality in IPF, and AEs also seem to cause significant mortality in other FILDs. [5][6][7][8][9][10][11][12][13][14] According to previous studies, every year about 5%-15% of patients with IPF will experience an AE. 5 13 Recently, it was shown that the incidence of AE or death in a study consisting of various types of patients with FILD was 7.8% per year.…”
Section: Introductionmentioning
confidence: 99%
“…The 2018 Japanese IPF treatment guidelines suggest that patients with AE-IPF should be treated with corticosteroids, including pulse therapy 15 . This is contradicted by the results of Mengshu et al, 16 who reported that high doses of corticosteroids are not bene cial for AE-ILD patients, and that the clinical outcomes of patients with AE-IPF mainly depend on the underlying clinical condition and the extent of lung injury from the AE. Thus, there remains a lack of consensus regarding proper treatment of AE-ILD.…”
Section: Discussionmentioning
confidence: 86%